2003
DOI: 10.1038/sj.onc.1207027
|View full text |Cite
|
Sign up to set email alerts
|

DroVav, the Drosophila melanogaster homologue of the mammalian Vav proteins, serves as a signal transducer protein in the Rac and DER pathways

Abstract: Mammalian Vav signal transducer proteins couple receptor tyrosine kinase signals to the activation of the Rho/Rac GTPases, leading to cell differentiation and/or proliferation. The unique and complex structure of mammalian Vav proteins is preserved in the Drosophila melanogaster homologue, DroVav. We demonstrate that DroVav functions as a guanine-nucleotide exchange factor (GEF) for DRac. Drosophila cells overexpressing wildtype (wt) DroVav exhibited a normal morphology. However, overexpression of a truncated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
1
15
1
Order By: Relevance
“…pathways in other tissues of C. elegans, as well as in Drosophila and mammalian cells (Margolis et al 1992;Dekel et al 2000;Pandey et al 2000;Hornstein et al 2003;Norman et al 2005). However, our data are the first to suggest Vav interaction with EGFR or PLCg in neurons.…”
Section: Discussioncontrasting
confidence: 43%
“…pathways in other tissues of C. elegans, as well as in Drosophila and mammalian cells (Margolis et al 1992;Dekel et al 2000;Pandey et al 2000;Hornstein et al 2003;Norman et al 2005). However, our data are the first to suggest Vav interaction with EGFR or PLCg in neurons.…”
Section: Discussioncontrasting
confidence: 43%
“…The single Drosophila vav ortholog possesses the same catalytic and regulatory properties as its mammalian counterparts (Couceiro et al, 2005). In addition, the Drosophila Vav is tyrosine phosphorylated in response to EGF stimulation in S2 cells (Hornstein et al, 2003;Margolis et al, 1992). Furthermore, a yeast two hybrid analysis has shown that the SH2-SH3 region of Vav can bind the epidermal growth factor receptor (EGFR) and the intracellular domain of PVR, PVRi, but not a kinase-dead version of PVRi, suggesting that Vav SH2-SH3-HA::PVRi interactions depend on PVR autophosphorylation (Bianco et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…We also identified three genes (glutathione S-transferase, Cytochrome p450 and Gluthathione-requiring prostaglandin D synthase) that are under the control of Ci-ERK and are orthologues of or closely related to genes expressed in papillae of the ascidians RESEARCH ARTICLE Development 134 (6) Herdmania curvata that have been implicated in metamorphosis and are downstream genes of the EGF-like Hemps pathway (Woods et al, 2004;Arnold et al, 1997). Although it is not known whether Hemps activates ERK, it is tempting to speculate that it does, because activation of the Ras/Raf/ERK pathway by EGF is well described in many species (Hornstein et al, 2003). Moreover, our identification of genes controlled by Ci-ERK in papillae, the observation that metamorphosis does not occur with MEK inhibition and data on Hemps in H. curvata that shows that it induces settlement and metamorphosis (Eri et al, 1999) are consistent with our observations that one of the effects of the Hemps pathway is to activate the ERK cascade in papillae cells.…”
Section: Genes Modulated By Jnk And/or Erkmentioning
confidence: 99%